FAKTOR SOSIODEMOGRAFI DAN PERILAKU YANG BERHUBUNGAN DENGAN KEJADIAN FILARIASIS DI KABUPATEN KUNINGAN - Icca Stella Amalia; Nissa Noor Annashr (Universitas YPIB Majalengka, 2018)
Filariasis is an infectious disease that still become public health problem in Indonesia. In 2013 there were 12,714 cases and by 2014 there were 14,932 cases in Indonesia. Kuningan is one of the districts that become filariasis endemic areas in West Java Province. The objectives of the research was to analyze the sosiodemographic and behavior factors that associated with filariasis. This research was analytic survey approach with case control study. The population of this research were all of case filariasis in Kuningan in 2017. There were 16 cases of filariasis in Kuningan so all of them were taken as sample. Sampling for control groups conducted with purposive sampling technique. The cases of these research and the controls were 48 respondents. The ratio of cases to the controls 1 : 2 (16 cases : 32 controls). Data collection was taken by observation and interview. After the collected the data, it was analyzed by univariate and bivariate analysis by using chi-square test. The result showed that 48 respondents (18 man and 30 woman) with mean 49.1 years old. Independent variabel consist of sosiodemographic (sex, level of education, level of knowledge, type of job, and income) and behavior variable (habit of going out at night, habbit of using repellent, habit of using mosquito net). Bivariate analysis showed that level of knowledge that had significant relationship with filariasis (p = 0.006 OR = 6.943). Based oh the result of this research, it suggested to Dinas Kesehatan Kuningan to improve health promotion program for community.